Karel Janeček − a leading figure in Czech Music Theory and Pedagogy: his theoretical writings from the 1930s and 1940s - Miloš Hons (Zeitschrift der Gesellschaft für Musiktheorie)
Karel Janeček (1903–1974) was a groundbreaking figure in Czech modern music theory. Although he was active as a scholar and a composer, his place in Czech music history rests on his theoretical work. He was the originator of a new model for university-level music theory teaching, setting up a framework whose essence is still in use today. After a brief period of teaching at the Prague Conservatory, he spent the following three decades of his career at the Academy of Performing Arts in Prague (AMU), where he was head of the Department of Music Theory. His work as a teacher of players, singers, conductors, music directors and, most notably, composers served Janeček as an empirical testing ground for the premises, concepts, and systemic principles he came to formulate in his major books and essays. Viewed from a historical perspective, his most significant books include Základy moderní harmonie (Modern Harmony, 1949, published 1965), Hudební formy (Musical Forms, 1955), and Tektonika – nauka o stavbě skladeb (Tectonics: A Theory of the Structure of Compositions, 1968). Janeček´s teaching commitments at AMU were centered around two theoretical courses whose concepts he drew up and put into practice: namely, Nauka o skladbě (Theory of Composition), which was later renamed Study of Compositions. With the passage of time, as Janeček brought out his essential theoretical writings, his theory of composition came to serve as an obligatory supplement to all disciplines of music theory. It was focused on three areas: (a) modern harmony, (b) melody, and (c) tectonics.